2015
DOI: 10.1002/ana.24393
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability and the risk of Parkinson disease: The Atherosclerosis Risk in Communities study

Abstract: Objectives Autonomic dysfunction frequently occurs in the context of Parkinson’s disease (PD) and may precede onset of motor symptoms. Limited data exist on the prospective association of heart rate variability (HRV), a marker of autonomic function, with PD risk. Methods We included 12,162 participants of the Atherosclerosis Risk in Communities (ARIC) study, a community-based cohort, without a diagnosis of PD at baseline (1987-89) and with available HRV data (mean age 54, 57% women). A 2-minute electrocardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 25 publications
4
64
1
Order By: Relevance
“…ACCEPTED MANUSCRIPT 8 HRV is also associated with RBD [11,12], a well-known precursor of LBD, and can predict conversion to PD in elderly [17,18], suggesting that cardiac autonomic dysfunction occurs during the premotor stage of PD. Further, HRV is reported to correlate with other known LB markers, such as changes in olfaction and cardiac MIBG findings [11,[25][26][27].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…ACCEPTED MANUSCRIPT 8 HRV is also associated with RBD [11,12], a well-known precursor of LBD, and can predict conversion to PD in elderly [17,18], suggesting that cardiac autonomic dysfunction occurs during the premotor stage of PD. Further, HRV is reported to correlate with other known LB markers, such as changes in olfaction and cardiac MIBG findings [11,[25][26][27].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Heart rate variability (HRV), as determined by electrocardiography (ECG), is a simple and non-invasive method used to investigate cardiac autonomic abnormalities [10]. HRV is reduced in PD, DLB or RBD [11][12][13][14][15][16], and predictive of PD development in elderly [17,18], suggesting the utility of HRV as an early diagnostic tool in LBD. However, HRV has not been compared between ET and TDPD.…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature on the course of HRV decline related to PD is not entirely consistent. In fact, a recent cohort study found an increased risk of PD in subjects with low HRV indicating HRV impairment in prodromal disease stages [13]. This discrepancy among studies highlights our still limited understanding of cardiac autonomic dysfunction in PD.…”
Section: Discussionmentioning
confidence: 96%
“…In the prospective Atherosclerosis Risk in Communities study, which included 12,162 participants, one of the outcomes showed that a low HRV was associated with an increased risk of Parkinson disease [21]. Using HRV as a measure of VN activity, a number of studies have shown a relationship between poor VN activity and inflammatory conditions such as rheumatoid arthritis [22], atherosclerosis [23] and Crohn's disease [24].…”
Section: Decreased Parasympathetic Tone In Other Medical Conditionsmentioning
confidence: 99%